Those kids from Fawn Creek - Kelly, Erin Entrada (Greenwillow Books, 2022)
Every day passes by just like every other day in Fawn Creek, Louisiana--at least, that's how best friends-since-forever Dorothy Doucet and Greyson Broussard feel. The two girls consider themselves outside the typical seventh-grade groups--especially the self-proclaimed God Squad, and the Fawn Creek Royalty, and the Jocks--and that suits them just fine, since they have each other. Dorothy and Greyson have no reason to believe this year will be any different, until some new kid from Somewhere Else comes to town.